Biotin Transport and Accumulation by Cells of Lactobacillus plantarum II. Kinetics of the System - Waller, James R. (1965)
Waller, James R. (University of Cincinnati, Cincinnati, Ohio), and Herman C. Lichstein. Biotin transport and accumulation by cells of Lactobacillus plantarum. II. Kinetics of the system. J. Bacteriol. 90:853–856. 1965.—Bound biotin-saturated cells of Lactobacillus plantarum accumulated free biotin by a time-dependent process exhibiting substrate saturation phenomena in the presence and absence of glucose. Apparent K(m) and V(max) values determined in the presence and absence of glucose, respectively, from Lineweaver-Burk plots were found to be 31.5 and 7.72 mμm (K(m)) and 9.72 and 3.26 μμmoles per mg per min (V(max)). Free biotin transport per se appeared to be an energy-independent, mediated process, whereas the accumulation of large intracellular vitamin concentrations was energy-dependent. Internal free biotin was quantitatively converted to bound biotin. The rate and extent of bound biotin formation was slower than free biotin uptake, and dependent upon intracellular free biotin levels up to a saturating concentration.